Comunicação nas Micro e Pequenas Empresas: uma análise das práticas e estratégias comunicacionais - Wichmann, Janaina (2014)
This dissertation aims to analyze the practices and strategies of organizational communication of micro and small business in Brazil. We sought to investigate how companies communicate with different audiences and communicative practices are used to promote the retention and growth of micro and small businesses. To this end, the research, exploratory and descriptive, was based on a qualitative approach, using as the main instrument in-depth interviews with five small businesses that will serve as a resource to understand the practices and communication strategies of smaller companies. With the support of the existing literature in the field, were investigated typologies and traditional functions of organizational communication, paying particular attention to the changes with the advent of the web and social media.